A Case study in the adoption of ICT in teaching and learning at a Malaysian Smart School - Zaenab, S.Abdul Majeed (2014)
Over the past number of years there has been a move towards using ICT in teaching and learning in Malaysia. This study explores factors that affect secondary school teachers’ adoption of ICT in the teaching and learning environment in a Malaysian smart school. A self-administered questionnaire was issued to all teaching staff (n=73). A random sample of key teachers interviews (n=10) were also used to provoke more elaborate responses on the participants’ experience in using ICT for teaching and learning as well as to gain a deeper understanding of the reasons for the responses given in the questionnaire. Descriptive analysis (frequency and percentages) were performed, and non- parametric tests (binominal and chi-square tests) were conducted on the data collected from the questionnaires. The emerging themes from the interview data were recorded for analysis. The results revealed that the participants were at the Utilisation level of ICT adoption (Hooper & Rieber, 1999). Most of them have a positive attitude toward ICT adoptions; they were willing and interested to use ICT, specifically computers in the classroom. The participants used ICT tools to prepare exam materials, content, worksheets and handouts for their teaching. They also used the internet and internet-based applications for sharing ideas/ resources for teaching and learning, and communication with other teachers. In addition, the participants felt competent and confident when they used ICT in the classroom. However, it was also found that the participants felt that: (1) using ICT in teaching took up too much time, (2), the school management did not provide enough training to improve their ICT skills, and (3) even though the school management supported ICT adoption in teaching and learning but they did not put it as a priority. These factors were considered as barriers and there was a significant association (p <.05) between teachers` perception and barriers that teachers thought may affect ICT adoption. In conclusion, the findings indicate that the participants were positive about the adoption but several factors were barriers which that they were unable to progress from a lower level to a higher level of adoption. Recommendations include allocation of time to prepare ICT resources and lessons, further training for teachers and increase in the number of computers at the school.